Life on the hill: Students and the social history of Makerere - Mills, D (2006)
How will history judge British late-colonial efforts to export its model of higher education to Africa? In this article I challenge any simple interpretation of the 'Asquith Commission' university colleges - such as Makerere or University College Ibadan - as alien impositions or colonial intellectual 'hothouses'. Focusing on Makerere University in Uganda, and drawing on a variety of archival and personal sources, I show how its students and faculty engaged in an ambivalent recreation and subversion of the Western idea of the university and its foundational discourses. I suggest that the institution offered a space to question and debate the purpose of an African university education. Students and staff made use of their limited political autonomy to challenge and rework the colonial hierarchies of race and culture. As a result, Makerere remained an influential forum for intellectual debate, cultural expression and social critique until the mid-1970s. Whilst this legacy is made less visible by the subsequent years of political crisis, underfunding and expansion in student numbers, it remains an important historical legacy from which to rethink the future of African universities.